A causal model to assess the correlation between community vitality and community size of non-native ethnic groups in the Indian context - Purbita Samanta; Subrata Chattopadhyay; Archiman Biswas (Sustainable Futures)
This study examines the vitality factors influencing the change in community size of non-native ethnic groups in their urban environment. Despite the significant presence of non-native ethnic communities in urban areas, there is a lack of comprehensive research on their long-term settlement decisions and the factors that influence these decisions. This research aims to fill this gap by employing a binomial logistic regression analysis to explore the relationship between change in community size of the Chinese and Nepali communities in West Bengal, India and the community vitality factors. Data was collected through surveys targeting the subsequent generation members of these communities. The findings reveal that ethnic inclusivity, economic integration, neighbourhood safety, and government support significantly influence the decision to stay for both communities, though the strength and direction of these influences vary. The results align with global objectives to ensure reduced inequalities (SDG 10), promote decent work and economic growth (SDG 8), create sustainable cities and communities (SDG 11), and establish peace, justice, and strong institutions (SDG 16). Future research should explore these dynamics in other urban contexts and among other non-native ethnic communities and offer a broader understanding of urban integration and the factors that promote community vitality in diverse urban settings.